The Effects of submerged vanes inclination angle on sediment transport into sub-channel - mnaf adel; Ali N. Hilo (Wasit Journal of Engineering Sciences)
The sub-channels that branch from the larger rivers may be manmade or natural. From the major channels, these sub-channels transfer sediments and water. The deposition of sediments at the entrance, sub-channel is a significant research challenge because it threatens the sub-facilities channel's and reduces the sub-carrying channel's capacity. Therefore, submerged vanes were used to reduce the amount of sediment entering the sub-channel. The goal of the vanes is to reduce the amount of sediment entering the sub-channel, hence redistributing sediment at the sub-entry channel's . They are vertically aligned with the flow direction and tilted at a certain angle. A physical model of the main channel, a sub-channel at a right angle, and a sediment feeder mechanism were developed. 51 tests were undertaken, 3 with submerged vanes and 48 without, with a varying number of submerged vanes (7, 5, 3 and 1). And angling it at various angles (10˚, 20˚, 30˚, and 40˚) in the discharge direction and with three sub-discharges of (19.1, 27 and 30.5 l/s), the sediment concentration flow was (6 kg/h). The weights of the sediments in sub-channel were calculated, and it was found that there is an effective use of these vanes and that the least amount of sediments is achieved when the angle is (20ᵓ). It was observed that the performance of the submerged vanes was significantly improved when there was a decrease in the discharge of the sub-channel.